Plate 24: Device for raising water from a river or spring by river or canal current - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
Mechanics: undershot waterwheel; force pump; flap valve; double interrupted crown gears and lantern gear; worm and worm gear; lantern and crown gear; motion converter (rotating to linear).
Keywords: Pumping machinery; Reciprocating pumps; Water-power; Machinery